Lepidium sativum Seed Extract-Mediated Synthesis of Zinc Oxide Nanoparticles: Structural, Morphological, Optical, Hemolysis, and Antibacterial Studies - Adnan Alnehia; Annas Al-Sharabi; Abdel-Basit Al-Odayni; A. H. Al-Hammadi; Fares H. AL-Ostoot; Waseem Sharaf Saeed; Naaser A. Y. Abduh; Ali Alrahlah (Bioinorganic Chemistry and Applications)
Nanomaterials have unique physicochemical properties compared to their bulk counterparts. Besides, biologically synthesized nanoparticles (NPs) have proven superior to other methods. This work aimed to biosynthesize zinc oxide (ZnO) NPs using an aqueous extract of Lepidium sativum seed. The obtained ZnO NPs were characterized by X-ray diffraction, scanning electron microscopy, Fourier transform infrared, and ultraviolet-visible spectroscopy. The in vitro antibacterial activity of ZnO NPs against Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria was assessed using the disk diffusion technique. The hemolytic impact was quantified spectrophotometrically. The results indicated a 24.2 nm crystallite size, a hexagonal structure phase, and a 3.48 eV optical bandgap. Antibacterial studies revealed a dose-dependent response with comparable activity to the standard drug (gentamicin) and higher activity against S. aureus than E. coli, e.g., the zone of inhibition at 120 mg/mL was 23 ± 1.25 and 16 ± 1.00 mm, respectively. The hemolysis assay showed no potential harm due to ZnO NPs toward red blood cells if utilized in low doses. As a result, it could be concluded that the reported biogenic method for synthesizing ZnO NPs is promising, resulting in hemocompatible NPs and comparable bactericidal agents.